PENGARUH SUPLAI UDARA TERHADAP KARAKTERISTIK BENTUK DAN TEMPERATUR NYALA API DARI UAP PREMIUM - A'yan Sabitah; Moh. Sulhan; Ricky Indriyanto; Akhmad Syarief (INFO-TEKNIK, 2020)
The scarcity of LPG gas that often occurs in Indonesia often makes Indonesian citizens uneasy. This scarcity led many researchers to conduct research that could reduce the dependence of Indonesian citizens with LPG gas. In this study, researchers conducted tests related to the use of premium steam as fuel. This test is carried out by varying the air supply, where this supply has been determined at 2 km/cm2 , 3 km/cm2 and 4 km/cm2 , in addition to the air supply this test also performs fire temperature measurements using thermocouples and data logers, where the location of the thermocouple has been located at points 1 cm, 3cm and 5 cm from the mouth of the nozzle. Based on the test results, the shape of the flame from variations in the air supply obtained the best and stable results were in the 3 km/cm2 air supply, while the other for the 2 km/cm2 air supply was found to be unstable fire and for which the 4 km/cm2 fire air supply looked large and unstable. Whereas for the highest temperature of the three placement points the thermocouple is located at the top point with a distance of 5 cm from the mouth of the fire with an average temperature of around 900oC and the lowest temperature is at 1 cm from the nozzle mouth, where the temperature is at 400oC to 550oC, in addition The temperature stability is in the air supply of 3 km/cm2